Adolescent Plant Product Intake in Relation to Later Prostate Cancer Risk and Mortality in the NIH-AARP Diet and Health Study. Issue 10 (12th August 2021) - Lan, Tuo; Park, Yikyung; Colditz, Graham A; Liu, Jingxia; Wang, Molin; Wu, Kana; Giovannucci, Edward; Sutcliffe, Siobhan
ABSTRACT: Background: Although fruit and vegetable intake during adolescence, a potentially sensitive time period for prostate cancer (PCa) development, has been proposed to protect against PCa risk, few studies have investigated the role of adolescent plant product intake in PCa development. Methods: Intake of various vegetables, fruit, and grains by males at ages 12–13 y was examined in relation to later PCa risk and mortality in the NIH-AARP Diet and Health Study. Cox proportional hazards regression was used to calculate HRs and 95% CIs of nonadvanced ( n = 14, 238) and advanced ( n = 2, 170) PCa incidence and PCa mortality ( n = 760) during 1, 729, 896 person-years of follow-up. Results: None of the plant products examined were associated consistently with all PCa outcomes. However, greater adolescent intakes of tomatoes ( P -trend = 0.004) and nonstarch vegetables ( P -trend = 0.025) were associated with reduced risk of nonadvanced PCa, and greater intakes of broccoli ( P -trend = 0.050) and fruit juice ( P -trend = 0.019–0.025) were associated with reduced risk of advanced PCa and/or PCa mortality. Positive trends were also observed for greater intakes of fruit juice ( P -trend = 0.002), total fruit ( P -trend = 0.014), and dark bread ( P -trend = 0.035) with nonadvanced PCa risk and for greater intakes of legumes ( P -trend < 0.001), fiber ( P -trend = 0.001), and vegetable protein ( P -trend = 0.013–0.040) with advanced PCa risk or PCa mortality. Conclusions: Our findings do not provide strong evidence to suggest that adolescent plant product intake is associated with reduced PCa risk.